#TITLE_ALTERNATIVE# - KARLINA (NIM 13203010), RIAFENI
There are some ways that can be used to improve the quality of communication using OFDMA that is distorted as a result of frequency selective channel. In this final project, it will be cautioned the performance of OFDMA system that is using four kinds of optimization technique, those are the selectivity of user allocation technique, the using of frequency diversity, the turning of flat channel, and the using of convolutional coding. The impact of each optimization technique can be cautioned from Bit Error Rate (BER) that is occured in each user at the certain SNR. The value of BER is earned by simulating 4 users OFDMA system at frequency selective channel at downlink direction using computing program, MATLAB 7,0. The results of this simulation show that block allocation technique gives the best BER quality on the certain subchannel, but it also gives the worst quality on some other subchannels. On the otherhand, interleaved and random allocation give the quality that is extreamely the same at each subchannel from the certain user. Optimization using frequency diversity shows the improvement of the quality is not significant if it is compared by the result from the other optimization techniques. The formation of flat canal gives the significant improvement, and wipe off the influence of the selectivity of user allocation technique. Whereas, the convolutional coding gives the lowest BER value for each user at OFDMA system.